The role of gene fusions in the evolution of metabolic pathways: the histidine biosynthesis case - Fani, Renato; Brilli, Matteo; Fondi, Marco; Lió, Pietro (BMC evolutionary biology, 2007)
Histidine biosynthesis is one of the best characterized anabolic pathways. There is a large body of genetic and biochemical information available, including operon structure, gene expression, and increasingly larger sequence databases. For over forty years this pathway has been the subject of extensive studies, mainly in Escherichia coli and Salmonella enterica, in both of which details of histidine biosynthesis appear to be identical. In these two enterobacteria the pathway is unbranched, includes a number of unusual reactions, and consists of nine intermediates; his genes are arranged in a compact operon (hisGDC [NB]HAF [IE]), with three of them (hisNB, hisD and hisIE) coding for bifunctional enzymes. We performed a detailed analysis of his gene fusions in available genomes to understand the role of gene fusions in shaping this pathway. The analysis of HisA structures revealed that several gene elongation events are at the root of this protein family: internal duplication have been identified by structural superposition of the modules composing the TIM-barrel protein. Several his gene fusions happened in distinct taxonomic lineages; hisNB originated within gamma-proteobacteria and after its appearance it was transferred to Campylobacter species (epsilon-proteobacteria) and to some Bacteria belonging to the CFB group. The transfer involved the entire his operon. The hisIE gene fusion was found in several taxonomic lineages and our results suggest that it probably happened several times in distinct lineages. Gene fusions involving hisIE and hisD genes (HIS4) and hisH and hisF genes (HIS7) took place in the Eukarya domain; the latter has been transferred to some delta-proteobacteria. Gene duplication is the most widely known mechanism responsible for the origin and evolution of metabolic pathways; however, several other mechanisms might concur in the process of pathway assembly and gene fusion appeared to be one of the most important and common.